Realia as a specific component of non-equivalent vocabulary - Islomova, Matluba Isroil kizi (Science and Education, 2023)
One of the most difficult problem of translation is of course, in the possibility of adequate transfer of the content of a text from one language to another. Non-equivalent vocabulary occupies a special place in science of translation. It exists because it denotes national realias. It’s clear that non-equivalent vocabulary refers to the lexical units of the source language that don’t have direct matches in the vocabulary in the translating language. Sometimes such lexical units are called untranslatable, but this is true only in terms of formal translation using a dictionary. The article is devoted to the realia as a specific componenet of non-equivalent vocabulary. Translation of realities is part of a large and important problem of transferring national and historical originality, which probably goes back to the very birth of translation theory as an independent discipline.